Old Lithuanian ischtirra ‘found out’ and some notes on the development of Baltic preterit - Ostrowski, Norbert (Baltistica, 2019)
The starting point for our considerations on the development of the Baltic preterite is the Old Lithuanian preterite /ištira:/ ‘found out’, etymologically connected to týrė ‘examined’. In form, /ištira:/ and týrė match the Old Church Slavonic otьre (thematic aorist) and trь (sigmatic aorist). This, in turn, is an argument for the hypothesis proposed by Daniel Petit (2004) on the origin of the lengthening in the Baltic preterite. The second part of this paper discusses the traces of a coexistence of inflected aspect (based on the contrast of the past tenses of aorist : imperfect) and derivational aspect (based on the opposition of perfective : imperfective) in Lithuanian.
Keywords: Old Lithuanian; historical morphology; verb; aspect; tense